Breeding for polledness in cattle – Exploring potential side effects and sustainable breeding strategies in quantitative genetic, genomic and simulation studies - Scheper, Carsten; Justus Liebig University Giessen (My University, 2023)
Breeding for genetic polledness represents one of the alternatives to routine dehorning in dairy and beef cattle farming. Due to the increasingly critical perception of dehorning in the ongoing animal welfare debate, the search for alternatives is becoming more urgent. Since most dairy and dual-purpose cattle raised in Germany today are currently dehorned, intensifying the breeding for polledness is the most pragmatic alternative. As a result, polled breeding in the largest dairy and dual-purpose breeds in Germany, German Holsteins and Simmental, is experiencing increased demand and ongoing integration into existing breeding programs. Starting from very low allele frequencies, the proportion of polled animals has increased sharply over the past 10 years. Traditionally existing breeding value deficits of polled insemination bulls have decreased during this time. While most economically relevant traits in cattle breeding are quantitative traits, polledness is one of the few relevant qualitative traits. The inheritance of the trait at the polled locus on chromosome 1 of the bovine genome was described early on and has been intensively investigated and increasingly elucidated by molecular genetics over the past 20 years. However, recent research results show an increasingly complex picture with different structural or allelic variants at the locus locus. In addition, the precise influence of the known variants at the polled locus on physiological processes of horn growth towards are still unclear. In addition, there are further phenotypic phenomena such as the occurrence of scurs and double rows of cilia, which contribute to the complexity of the trait. The overall objective of this thesis was to investigate the phenotypic and genetic relationships between the trait polledness and other traits in light of the intensification of hornless breeding in the German Holstein and Simmental breeds. Besides performance traits, which are strongly relevant in current breeding programs, available functional traits were also considered. Classical quantitative genetic models (chapters 2 and 3) as well as methods adapted to genomic data (chapter 4) were used. In addition, stochastic simulation studies (chapter 5) were performed to evaluate selection strategies for intensification of polled breeding and their possible consequences on important parameters of breeding success. In chapters 2 and 3, single-gene effects of the polled locus were estimated for secondary traits in the Simmental breed with the application of adapted quantitative-genetic models, which take the monogenic structure of the trait into account. In both univariate and bivariate models, possible pleiotropic effects of the polled locus could be investigated in this way. While no direct effects of the polled locus were found for the majority of the studied performance and functional traits, a significant effect of the polled locus was found for the trait milk protein percentage. However, the genetic correlation estimated from bivariate models does not indicate an unfavorable genetic relationship in this regard. On the genomic level, the results obtained from the quantitative genetic analyses could be further confirmed (chapter 4). Using genomic data from the German Holstein breed, a comparison of polled and horned insemination bulls revealed selection signatures mainly in the proximal region of chromosome 1 near the polled locus. Significant associations to secondary traits could not be detected in genome-wide association studies based on breeding values. Within the framework of a stochastic simulation study (chapter 5), it could be shown that a rapid intensive selection for polledness is associated with substantial losses in genetic gain if the existing initial status-quo of the polled population is taken into account. Furthermore, due to the low initial allele frequencies, a completely polled breeding population can realistically only be achieved after > 5-10 generations. Regarding possible selection strategies, it could be shown that a sex-specific differentiated selection for the hornless phenotype on the female side and specifically for the hornless genotype (targeted homozygosity) on the male side seems to be promising. In summary, an intensification of polled breeding should strive for a balance between increasing the allele frequency of polledness while securing the genetic progress by adjusting the selection intensity and strategy. The present work contributes to a further in-depth study of polledness in cattle. While the molecular genetic structure has already been extensively studied, there has been a lack of work focusing on possible secondary effects of increased breeding for polledness. Even though the progressive intensification of polled breeding has just begun, some important questions concerning this process could be investigated on an already larger data base. In this sense, in the summary of the results of this thesis, indications that significant (negative) secondary effects of breeding for polledness are not to be expected, become stronger.
Keywords: cattle; polledness; quantitative genetics; simulation studies; selection signatures; ddc:630